The Validity, Reliability, and Feasibility of Measurement Tools Used to Assess Sleep of Pre-school Aged Children: A Systematic Rapid Review - Phillips, Sophie M.; Summerbell, Carolyn; Ball, Helen L.; Hesketh, Kathryn R.; Saxena, Sonia; Hillier-Brown, Frances C. (Frontiers in Pediatrics, 2021)
Background: Sleep of pre-school aged children is important for their health and development, but there are currently no standards for measuring sleep in this age group. We aimed to examine the validity, reliability and feasibility of tools used to assess sleep of pre-school aged children. Methods: Studies were eligible for inclusion if they examined the validity and/or reliability and/or feasibility of a measurement tool used to examine sleep of pre-school aged children (aged 3-7 years). We systematically searched six electronic databases, grey literature and trial registries. We manually searched topic specific journals, reference and citations of included studies, and reference lists of existing reviews. We extracted data and conducted a risk of bias assessment on the included studies using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) risk of bias checklist. We used a narrative synthesis to present the results. Results: Sixteen studies met the inclusion criteria: these explored accelerometers (n=3) and parental reported tools (n=13; 9 questionnaires, 6 diaries). Studies assessed construct validity (n=3), criterion validity (n=1), convergent validity (n=13), test-retest reliability (n=2), internal consistency (n=4) and feasibility (n=12). Most studies assessed the convergent validity of questionnaires and diaries compared with accelerometers, but the validity of accelerometers for sleep in this age group is unknown. Of studies with a low risk of bias, one sleep diary was shown to be valid for measuring sleep duration. No measurement tools were appropriate for determining sleep quality. Reporting of reliability and feasibility was minimal. Discussion: The evidence base in this field is limited, and most studies had high risk of bias. Future research on sleep in pre-school aged children should focus on assessing the validity, reliability and feasibility of accelerometers, which in turn will improve the quality of studies that assess questionnaires and diaries against accelerometers.